Sistem Informasi Inventory Barang Pada CV. Delta Power Listrindo Menggunakan Metode Buffer Stock dan Reorder Point (ROP) - Bisri, Cholil; Kurniawan, Rakhmat (Universitas PGRI Kanjuruhan Malang, 2025)
The inventory information system is a system that is very necessary and must be owned by a business agency and company. This system uses the buffer stock and reorder point (ROP) method which functions to predict the stock of goods and the amount of reordering goods. The information system used is a website that functions to improve the efficiency and effectiveness of stock management to improve accuracy and save operational costs in the company. CV. Delta Power Listrindo is a company engaged in the production and provision of electrical products both in industry and housing. This can make it easier for an agency and company to manage stock. The system also contains data on incoming goods reports, outgoing goods and data on goods submission reports that can be printed and used for backup data that can be stored by the company. Therefore, with this system, the company is expected to be able to reduce the risk of shortages or excess stock and improve the quality and quantity of service to customers and minimize errors.